Variation in physical and mechanical properties with coating thickness in epoxy-diamine-aluminum system - Goyanes, Silvia Nair (2005)
The mechanical properties and glass-transition temperature within different thickness organic coatings made of diglycidyl ether of bisphenol A epoxy resin and 3-aminomethyl-3,5,5-trirnethylcyclohexylamine hardener are determined. The coatings are deposited on aluminum alloy (1050) substrates after degreasing. Dynamic mechanical thermal analysis and differential scanning calorimetry experiments are carried out on debonded coatings before and after the material from the opposed surface to the polymer/metal interface is removed by polishing. The results clearly show that the values of the physical and mechanical properties in those coatings depend on their thickness, but there is no gradient of properties within such coatings. Therefore, at a given thickness, those properties are homogeneous within the coating. To gain a better fundamental understanding of this behavior, a qualitative model involving the chemical reactions that take place at the epoxy/metal interface and the related diffusion phenomena is given. © 2005 Wiley Periodicals, Inc.